2018
DOI: 10.1089/dna.2017.3926
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Downregulation of miR-335-5p by Long Noncoding RNA ZEB1-AS1 in Gastric Cancer Promotes Tumor Proliferation and Invasion

Abstract: Recently, long noncoding RNAs (lncRNAs) have emerged as new gene regulators and prognostic biomarkers in several cancers, including gastric cancer (GC). In this study, we investigate the role of lncRNA ZEB1 antisense1 (ZEB1-AS1) on GC progression. In the present study, we found that ZEB1-AS1 expression was upregulated in GC tissues and cell lines. High ZEB1-AS1 expression was significantly correlated with advanced TNM stage, lymph node metastasis, and poor overall survival in GC patients. ZEB1-AS1 suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Meanwhile, the in vitro experiment by Zhang et al [31] also found the obviously reduced invasion ability of gastric cancer cells in vitro after inhibition of ZEB1-AS1. In the current investigations, the migration and invasion abilities of Hela cells were significantly decreased when transfected with the siRNA of ZEB1-AS1.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, the in vitro experiment by Zhang et al [31] also found the obviously reduced invasion ability of gastric cancer cells in vitro after inhibition of ZEB1-AS1. In the current investigations, the migration and invasion abilities of Hela cells were significantly decreased when transfected with the siRNA of ZEB1-AS1.…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al showed the tumor‐promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR‐331‐3p. In addition, expression of several miRNAs, including miR‐675, miR‐145‐5p, miR‐152, miR‐145, miR‐23b‐3p, and miR‐335‐5p, are significantly dysregulated by lncRNAs and then change the expression of target mRNAs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐335 has been confirmed to serve as a master suppressor in BC . Also, miR‐335‐5p, an aberrantly expressed miRNA, could be a major monitor in the progression of gastric cancer . However, there is little knowledge of the molecular mechanism by which miR‐335‐5p regulates biological development.…”
Section: Introductionmentioning
confidence: 99%
“…20 Also, miR-335-5p, an aberrantly expressed miRNA, could be a major monitor in the progression of gastric cancer. 21 However, there is little knowledge of the molecular mechanism by which miR-335-5p regulates biological development. In several studies, MiRNAs have been reported to bind to the 3 0untranslated region (3'-UTR) of the target mRNA, thereby leading to translational reduction or mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%